
∫(0→π/2) [(sint)^4-(sint)^6] dt
1个回答
展开全部
这里用一个公式会简单些:∫ [0--->π/2] f(sinx)dx=∫ [0--->π/2] f(cosx)dx
∫[0→π/2] (sin⁴t-sin⁶t) dt
=∫[0→π/2] sin⁴t(1-sin²t) dt
=∫[0→π/2] sin⁴tcos²t dt
=1/2( ∫[0→π/2] sin⁴tcos²t dt+∫[0→π/2] sin²tcos⁴t dt )
=1/2 ∫[0→π/2] sin²tcos²t(sin²t+cos²t) dt
=1/2 ∫[0→π/2] sin²tcos²tdt
=1/8 ∫[0→π/2] sin²2tdt
=1/8 ∫[0→π/2] (1-cos4t)dt
=1/8(t-1/4sin4t) [0→π/2]
=π/16
∫[0→π/2] (sin⁴t-sin⁶t) dt
=∫[0→π/2] sin⁴t(1-sin²t) dt
=∫[0→π/2] sin⁴tcos²t dt
=1/2( ∫[0→π/2] sin⁴tcos²t dt+∫[0→π/2] sin²tcos⁴t dt )
=1/2 ∫[0→π/2] sin²tcos²t(sin²t+cos²t) dt
=1/2 ∫[0→π/2] sin²tcos²tdt
=1/8 ∫[0→π/2] sin²2tdt
=1/8 ∫[0→π/2] (1-cos4t)dt
=1/8(t-1/4sin4t) [0→π/2]
=π/16
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询